Remoteness and maternal and child health service utilization in rural Liberia: A population-based survey - Avi Kenny; Gaurab Basu; Madeleine Ballard; Thomas Griffiths; Katherine Kentoffio; Jean Bosco Niyonzima; G. Andrew Sechler; Stephen Selinsky; Rajesh R. Panjabi; Mark J. Siedner; John D. Kraemer (Edinburgh University Global Health Society, 2015)
This study seeks to understand distance from health facilities as a barrier to maternal and child health service uptake within a rural Liberian population. Better understanding the relationship between distance from health facilities and rural health care utilization is important for post-Ebola health systems reconstruction and for general rural health system planning in sub-Saharan Africa.